Relationship Marketing terhadap Customer Retention pada Warung Langsam 13 Garut - Tatang Mulyana; Intan Tenisia Prawita; Vina Gunawan (Fakultas Ekonomi Universitas Garut, 2019)
The purpose of this study was to determine the effect of relationship marketing on customer retention at Warung Langsam 13 Garut. The hypothesis used in this study is that there is a relationship marketing effect on customer retention at Warung Langsam 13 Garut. This research uses a descriptive method. The respondents from this study were 97 respondents who were selected using simple random sampling technique. The analysis technique used in this study is the validity and reliability test, simple linear regression analysis, and hypothesis testing using SPSS Software. The conclusion of this study is that there is an effect of relationship marketing on customer retention at Warung Langsam 13 Garut. This means that the better the relationship marketing that is done by a company, the more customer retention in the company. To have loyal customers, the company must strive to maintain it. Customer retention will bring benefits in this case long-term income, in addition to supporting the company's programs, both in the form of developing new products and services provided by the company